Nanotechnology and osteoarthritis; part 1: Clinical landscape and opportunities for advanced diagnostics. Issue 3 (14th September 2020) - Lawson, Taylor B.; Mäkelä, Janne T.A.; Klein, Travis; Snyder, Brian D.; Grinstaff, Mark W.
Abstract: Osteoarthritis (OA) is a disease of the entire joint, often triggered by cartilage injury, mediated by a cascade of inflammatory pathways involving a complex interplay among metabolic, genetic, and enzymatic factors that alter the biochemical composition, microstructure, and biomechanical performance. Clinically, OA is characterized by degradation of the articular cartilage, thickening of the subchondral bone, inflammation of the synovium, and degeneration of ligaments that in aggregate reduce joint function and diminish quality of life. OA is the most prevalent joint disease, affecting 140 million people worldwide; these numbers are only expected to increase, concomitant with societal and financial burden of care. We present a two‐part review encompassing the applications of nanotechnology to the diagnosis and treatment of OA. Herein, part 1 focuses on OA treatment options and advancements in nanotechnology for the diagnosis of OA and imaging of articular cartilage, while part 2 (10.1002/jor.24842) summarizes recent advances in drug delivery, tissue scaffolds, and gene therapy for the treatment of OA. Specifically, part 1 begins with a concise review of the clinical landscape of OA, along with current diagnosis and treatments. We next review nanoparticle contrast agents for minimally invasive detection, diagnosis, and monitoring of OA via magnetic resonace imaging, computed tomography, and photoacoustic imaging techniques as well as for probes for cell tracking. We conclude by identifying opportunities for nanomedicine advances, and future prospects for imaging and diagnostics.